Utilization of waste biomass for the synthesis of functionalizable support for covalent anchoring of active organo catalyst - Doke, D. S.; Advani, J. H.; Naikwadi, D. R.; Gawande, M. B.; Walke, P.; Umbarkar, S. B.; Biradar, A. V. (ACS Sustainable Chemistry & Engineering, 2019)
A single step synthetic procedure for carbon microspheres from agricultural waste residue (sugarcane bagasse) by low-temperature hydrothermal carbonization using oxalic acid as a hydrating/dehydrating agent is developed. The FTIR and XPS spectroscopy analysis indicates the presence of −OH, −COOH, and C═O functional groups on the surfaces of carbon spheres. These functional groups of the carbon spheres were utilized as a novel route to anchor 3-aminopropyl-triethoxysilane and 3-(2-aminoethylamino)propyl)-trimethoxysilane via condensation of triethoxy/trimethoxy silanes for the synthesis of organo base supported on carbon catalysts. The catalytic activity of the obtained supported organo-base catalyst was demonstrated for C–C bond forming (Henry) reaction. Among all prepared catalysts, 3-(2-aminoethylaminopropyl)-trimethoxysilane grafted in toluene showed high conversion (up to 100%) of aldehydes with excellent selectivity toward β-nitrostyrene. The catalyst was reused five times without losing significant activity for the same reaction.